Reforming options for hydrogen production from fossil fuels for PEM fuel cells - ÖZDOĞAN, ZEYNEP SİBEL (ELSEVIER, 2006)
PEM fuel cell systems are considered as a sustainable option for the future transport sector in the future. There is great interest in converting current hydrocarbon based transportation fuels into hydrogen rich gases acceptable by PEM fuel cells on-board of vehicles. In this paper, we compare the results of our simulation studies for 100 kW PEM fuel cell systems utilizing three different major reforming technologies, namely steam reforming (SREF), partial oxidation (POX) and autothermal reforming (ATR). Natural gas, gasoline and diesel are the selected hydrocarbon fuels. It is desired to investigate the effect of the selected fuel reforming options on the overall fuel cell system efficiency, which depends on the fuel processing, PEM fuel cell and auxiliary system efficiencies. The Aspen-HYSYS 3.1 code has been used for simulation purposes. Process parameters of fuel preparation steps have been determined considering the limitations set by the catalysts and hydrocarbons involved. Results indicate that fuel properties, fuel processing system and its operation parameters, and PEM fuel cell characteristics all affect the overall system efficiencies. Steam reforming appears as the most efficient fuel preparation option for all investigated fuels. Natural gas with steam reforming shows the highest fuel cell system efficiency. Good heat integration within the fuel cell system is absolutely necessary to achieve acceptable overall system efficiencies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: fuel reforming; PEM fuel cell; hydrogen production; NATURAL-GAS; TRANSPORT APPLICATIONS; GENERATION; VEHICLES; SYSTEMS; TEMPERATURE; PROCESSORS; CATALYSTS; METHANE